An overview on synthetic administrative data for research - Theodora Kokosi (International Journal of Population Data Science, 2022)
Use of administrative data for research and for planning services has increased over recent decades due to the value of the large, rich information available. However, concerns about the release of sensitive or personal data and the associated disclosure risk can lead to lengthy approval processes and restricted data access. This can delay or prevent the production of timely evidence. A promising solution to facilitate more efficient data access is to create synthetic versions of the original datasets which do not hold any confidential information and can minimise disclosure risk. Such data may be used as an interim solution, allowing researchers to develop their analysis plans on non-disclosive data, whilst waiting for access to the real data. We aim to provide an overview of the background and uses of synthetic data, describe common methods used to generate synthetic data in the context of UK administrative research, propose a simplified terminology for categories of synthetic data, and illustrate challenges and future directions for research.